Prevalence of hypertension and its socio-demographic factors among adult population in a rural community of Singur block, Hooghly district, West Bengal - Karmakar, Nabarun; Naiya, Sourav; Saha, Indranil; Sinha, Rabindranath; Sahoo, Sanjaya Kumar; Dasgupta, Aparajita (International Journal Of Community Medicine And Public Health, 2017)
Background: Non-communicable diseases (NCD) are the leading cause of adult mortality and morbidity worldwide now days. The NCD like hypertension is emerging as a major health problem in India with increasing prevalence significantly in both urban and rural population. The objectives of the study were to find out the prevalence of hypertension and its association with socio-demographic factors among the study subjects, if any. Methods: This cross-sectional study was conducted from May, 2013 to April, 2014 in rural communities of Singur block among 651 individuals, aged 20 years or above of both sexes except pregnant and seriously ill subjects. Data were collected about education, type of family, family history of hypertension, income etc. Results: The overall prevalence of hypertension was 26.1% (male 21.8% and female 29.9%). Prevalence increased with increase in age group. Muslim religion, less education and sedentary life styles were found to be significantly associated with hypertension; while socio-economic status had no association with hypertension. Conclusions: The prevalence of hypertension in the rural population was found to be on the higher side compared to previous reports from India. Strong public health measures need to be seriously implemented to combat hypertension and its consequences.